Optimalisasi Media Digital TikTok sebagai Layanan Informasi Bimbingan Konseling Berbasis Dakwah - Fanan, M. Athoiful; Alfarisyi, Achmad Lutfi; Salsabila, Jihan Assyifa; Ariella, Sahda Diva (Jurnal Bimbingan dan Konseling Islam, 2023)
The digital era is an era where social media users can access everything quickly. Social media, one of which is TikTok, is believed to be a more contemporary and very effective media when compared to other information dissemination media. This research aims to determine the development of TikTok digital media for the purposes of da'wah-based counseling and guidance information services. The method used is library research with descriptive methods as the analysis technique. The results obtained from this research are that TikTok is considered to be a medium for delivering effective and efficient preaching-based counseling information in the digital era. This is because TikTok is a social media that is able to produce short videos with interesting features, so that it can attract a lot of attention from other users.